APLIKASI PEMBELAJARAN SISWA SEKOLAH DASAR MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) - Yusuf Sumaryana; Missi Hikmatyar (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
Learning models using computer technology should be developed in the present. Computers as a part of technology are currently developing their functions. Students can easily operate and carry out learning activities using computer technology. One of the facilities that can be used is multimedia computer technology where students can use interactive multimedia learning software. Multimedia is used as a learning tool which is expected to increase student interest in learning, because it consists of audio-visual elements. The Multimedia Development Life Cycle (MDLC) is a method used in this study for multimedia-based software development. Where there are 6 (six) stages that must be carried out in the implementation process. Adobe CS is used to create multimedia applications that have been designed